PHYSICAL AND PHYTO-CHEMICAL EVALUATION OF GLYCYRRHIZA GLABRA LINN (YASHTIMADHU) - B. S, *Indhu; Shajahan, M.A.; Hameed, A. Shahul (International Journal of Ayurveda and Pharma Research, 2018)
Glycyrrhiza glabra Linn (Yashtimadhu) is a perennial herb commonly known as liquorice. The drug is used in many Ayurvedic formulations like Dasamoolarishtam, Aswagandharishtam, Phalasarpighrita, Khadiragulika, Madhuyastyaditaila etc. Ascertaining the identity, genuineness and purity of herbal drugs has an important role in the maintenance of the quality of the drug and its formulations. The present study was undertaken to assess the preliminary Phyto-chemical constituents of the drug. The preliminary phyto-chemical analysis including quantitative data, qualitative chemical analysis, Thin Layer Chromatography, High Performance Thin Layer Chromatography and Atomic Absorption Spectroscopy were determined. The preliminary Phyto-chemical characteristics observed in the herb may help in standardization, identification and in carrying out further research in Glycyrrhiza glabra Linn.